Belajar enzim dari rumah; Penguatan Pembelajaran Berbasis Praktikum Pada Guru Di Sekolah Menengah Atas Kabupaten Tulangbawang - Arifiyanto, Achmad; Sumardi, Sumardi; Ekowati, Christina Nugroho (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2021)
Learning from home in the midst of the Covid-19 pandemic is a challenge in carrying out the learning process. Practical activities often have to be eliminated. In fact, practices are an alternative for student learning to better understand the conceptual material being taught. Enzyme practices program with material constraints, learning media to support Biology practices in Senior High Schools are the reasons for the need for this training. Through this training, the teacher can develop enzyme materials obtained by students from around their homes. Practical materials become more diverse, because they are developed with factors that affect enzyme performance. Educators are more familiar with the kahoot application and teachers are able to use the kahoot application as a practice-based learning evaluation media. It is also hoped that teacher creativity can develop to deal with the learning obstacles they experience.